Implementation of Augmented Reality (AR) Animation Media to Enhance Learning Outcomes and Interest in the Excretory System Topic - Nanda Oktavianda; Hafnati Rahmatan; Ismul Huda; Andi Ulfa Tenri Pada; Safrida; Rini Deviani (Jurnal Penelitian Pendidikan IPA, 2024)
The excretory system material requires visualization to enhance understanding. To help students grasp the concepts of the excretory system more effectively, the various organs of the excretory system must be illustrated in the learning material. Therefore, learning animations are needed that can display images created with augmented reality media, appearing almost lifelike in 3D form. This study aims to analyze the application of augmented reality animation media in improving learning outcomes and the difference in students' interest before and after learning about the excretory system with augmented reality animations. The method used is a quasi-experiment with a pretest-posttest control group design. The sample consists of 54 students from SMA Negeri 1 Ingin Jaya Aceh Besar, selected using random sampling techniques. Data were collected through multiple-choice tests and a questionnaire on students' interest in the excretory system material. The data were analyzed using a t-test, showing a significant difference in learning outcomes in the experimental class with a p-value < 0.05 (0.022 < 0.05), and a significant difference in students' interest before and after the learning process in the experimental class with a t-test result of p < 0.05 (0.037 < 0.05). It can be concluded that the application of augmented reality media can enhance learning outcomes and affect students' interest in the excretory system material.